PEMBARUAN PENDIDIKAN ISLAM DI MAKASSAR; STUDI KASUS PESANTREN MODERN PENDIDIKAN AL QUR’AN IMMIM TAMALANREA MAKASSAR (Sebuah Critical Review atas Disertasi Karya Muljono Damopolii) - Cahaya Khaeron (Universitas Muhammadiyah Metro, 2017)
The existence of a scientific work is the main thing that must be owned by the higher education world. In this case, the existence of a college will be determined by how high the productivity of scientific works produced by academics in it. The high scientific work is of course must be followed with the quality of the resulting quality. One way to measure the quality of a scientific work is through a critical review. The important role of critical review of scientific work is not just a report or writing about the contents of a scientific article alone, but rather to evaluation, such as reviewing or reviewing, interpreting and re-analyzing a scientific work. This paper attempts to provide a critical review model for a scientific work, in which case a dissertation by Muljono Damopolii is chosen. The method used in this study is a critical-analysis method, with systematization of the following steps; Briefly describe Muljono Damopolii's thoughts and views on his dissertation; Conducting critical analysis both in terms of theory and methodological aspects of the ideas that have been produced Muljono Damopolii in his dissertation related to the issue of renewal of Islamic education in the Modern School of Education Al Quran IMMIM Tamalanrea Makassar; Providing a new offer in terms of both theory and methodological to the dissertation of Muljono Damopolii's work.